Pengaruh Intellectual Capital, Managerial Entrenchment dan Firm Performance Terhadap Financial Statement Fraud - Claudia, Hadijah Ayu; Dewi, R Rosiyana (Jurnal EMT KITA, 2023)
This study aims to analyse the effect of Intellectual Capital, Managerial Entrenchment, Profitability, and Leverage on Financial Statement Fraud. A quantitative approach is used in this study. The financial statements of companies traded on the Indonesia Stock Exchange (IDX) are used as a source for secondary data collection in this study by focusing on the Consumer NonCyclicals sector covering 2019 to 2022. Sampling was carried out using purposive sampling method with a final number of 51 companies included as samples in this study. So that this study produced a total of 204 data samples. The analysis method used by researchers is the Logistic Regression method. From the results of the research that has been done, it shows that the Intellectual Capital Variable has no effect on Financial Statement Fraud, while the Managerial Entrenchment Variable has no effect on Financial Statement Fraud. Meanwhile, the Profitability Variable has a negative effect on Financial.